Antibacterial and Antifungal Activities of Linear and Cyclic Peptides Containing Arginine, Tryptophan, and Diphenylalanine - David Salehi; Eman H. M. Mohammed; Naiera M. Helmy; Keykavous Parang (Antibiotics)
Background. We have previously reported peptides composed of sequential arginine (R) residues paired with tryptophan (W) or 3,3-diphenyl-L-alanine residues (Dip), such as cyclic peptides [R4W4] and [R4(Dip)3], as antibacterial agents. Results. Herein, we report antibacterial and antifungal activities of five linear peptides, namely ((DipR)4(WR)), ((DipR)3(WR)2), ((DipR)2(WR)3), ((DipR)(WR)4), and (DipR)4R, and five cyclic peptides [(DipR)4(WR)], [(DipR)3(WR)2], [(DipR)2(WR)3], [(DipR)(WR)4], and [DipR]5, containing alternate positively charged R and hydrophobic W and Dip residues against fungal, Gram-positive, and Gram-negative bacterial pathogens. The minimum inhibitory concentrations (MICs) of all peptides were determined by the micro-broth dilution method against Methicillin-Resistant Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus, Enterococcus faecium, Enterococcus faecalis, Streptococcus pneumoniae, and Bacillus subtilis. Fungal organisms were Candida albicans, Candida parapsilosis, and Aspergillus fumigatus. [DipR]5 and ((DipR)2(WR)3) showed MIC values of 0.39–25 µM and 0.78–12.5 µM against Gram-positive and Gram-negative bacteria strains, respectively. The highest activity was observed against S. pneumoniae with MIC values of 0.39–0.78 µM among tested compounds. [DipR]5 demonstrated MIC values of 6.6 µM against C. parapsilosis and 1.6 µM against A. fumigatus, whereas fluconazole showed MIC values of 3.3 µM and >209 µM, respectively. Conclusions. These findings highlight the potential of these peptides as broad-spectrum antimicrobial agents.